Synthesising solver structure of the OpenFOAM mathematical modeling system for analysing thermal mode of LED lamps - Volodymyr Trofimov; Igor Sobianin (Tekhnologiya i Konstruirovanie v Elektronnoi Apparature)
Today LED lamps are used more and more widely in various fields of human activity. The operation of LEDs substantially depends on the thermal dissipation power and temperature. In this regard, one of the mandatory stages in the process of creating such lamps is the analysis of their thermal mode, which is necessary for the development of a heat sink. In order to analyze the thermal mode and design the heat sink for powerful LED lamps, the authors synthesized the structure of the problem solver. The new structure was based on the structure of the basic laplacianFoam solver and the application of the swak4foam library functions, which is a part of the OpenFOAM computational fluid dynamics toolbox. The results of the thermal mode simulation of the LED thermal model (a plate with a rectangular heat source) obtained using a modified solver were compared with those obtained by the proprietary solver of the CAD/CAE SolidWorks system and those obtained by analytical computation. The data adequacy of the modified solver was estimated and its practical application verified. The thermal mode of the Samsung LC009D LED, which is placed on the flat-plate finned heat sink, was analyzed. The Kaufer 5204 glue ability to be used in such design with natural convection cooling of the heat sink was tested. The glue thickness was 0.1 mm and its thermal conductivity was 1,5 W/(m·K). The heat sink's heat transfer coefficient was 10 W/(m2·K). The paper presents corresponding temperature distributions and shows that the new technique can be used for solving problems that arise when designing LED lamps.